1998
DOI: 10.1046/j.1365-2354.1998.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression in cancer patients: a literature review

Abstract: It is estimated that 20-25% of cancer patients suffer often unrecognized and untreated long-term depression, a condition that can make life miserable. Symptoms can include: lack of sleep; loss of interest in life; anxiety; irritation; loss of concentration; and, in severe cases, thoughts of suicide; leading to an overall poor quality of life. Given that the majority of patients diagnosed with clinical depression can be effectively treated with one form of treatment or another (psychological, pharmacological or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 53 publications
2
88
0
12
Order By: Relevance
“…As presented, spirituality is associated with optimism, and optimism is associated with depression. Building on findings from previous studies that examine (1) the relationship between spirituality and optimism, and (2) the relationship between optimism and depression, the current study attempts to link the two relationships. To date, only one known study examines the mediating role of optimism in the relationship between spirituality and depression.…”
Section: The Mediating Role Of Optimism In the Association Between Spmentioning
confidence: 99%
See 2 more Smart Citations
“…As presented, spirituality is associated with optimism, and optimism is associated with depression. Building on findings from previous studies that examine (1) the relationship between spirituality and optimism, and (2) the relationship between optimism and depression, the current study attempts to link the two relationships. To date, only one known study examines the mediating role of optimism in the relationship between spirituality and depression.…”
Section: The Mediating Role Of Optimism In the Association Between Spmentioning
confidence: 99%
“…Depression is a common mental health issue experienced by cancer patients, 1) which can lead to patients' overall poor quality of life. 1,2) Studies have identified multiple risk factors for depression in cancer patients such as patients' symptom levels, functional impairments, and fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and depression, known as the most common factors influencing sleep quality, are also the most prevalent psychiatric disorders faced by patients with malignancy [17,18]. Keeping these in mind, we evaluated sleep quality in the patients with the GERD by comparison of their sleep quality scores with those of patients with malignancy, which themselves were reported to have sleep problems.…”
Section: Introductionmentioning
confidence: 99%
“…This review also found that among gastric cancer the rates of depression varies from 13%-50% which is similar to earlier reports 10 . Methodological issues such as lack of standardization in terms of population studied, type of cancer, disease stage, sample size, assessment instruments, cutoff score, type of interview, and diagnostic criteria employed (including post traumatic stress disorder, major depression on the clinical scale as to stress symptoms and depressive symptoms on a self rated assessment scales) all contributed to the large variance in reported prevalence among these studies [10][11][12] . Additionally, the information about depression rates among gastric cancer is scarce in comparison to breast cancer [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%